Magnetic Resonance Imaging of Mammalian Cells Individually Expressing Membrane-Associated Magnetosome Proteins I, L, B, and E - Qin Sun PhD; Gabriel Varela-Mattatall PhD; Prushoth Vivekanantha PhD; Moeiz Ahmed PhD; Salvan Hassan PhD; Selinia Hong PhD; Neil Gelman PhD; R. Terry Thompson PhD; Frank S. Prato PhD; Donna E. Goldhawk PhD (Molecular Imaging)
The magnetosome, a membrane-bound iron biomineral formed within magnetotactic bacteria, is a unique model for a magnetic resonance imaging (MRI) reporter gene contrast agent. We are translating this technology to mammalian cells by expressing essential magnetosome genes mamI, mamL, mamB, and mamE into MDA-MB-435 human melanoma cells. Currently, these genes are individually expressed in the cell although the future goal is to express all four genes together. We examined the influence of these genes on cellular MRI relaxation rates by culturing cells in the presence and absence of iron-supplemented medium and scanning them at 3 Tesla using a gelatin phantom. Total cellular iron was measured by inductively-coupled plasma mass spectrometry and correlated with relaxation rates obtained from phantom experiments. Apart from mamE , magnetosome genes that are individually expressed in mammalian cells grown in iron supplement significantly affected cellular transverse relaxation rates compared to cells grown without iron supplement. Interestingly, mamI, mamL, mamB, and mamE (even though the latter had no effect on relaxation rate) significantly affected cellular iron content. This developing gene-based contrast agent will equip MRI with improvement to imaging sensitivity and the technology to track cellular activities long term.